Traduciendo el aprendizaje profesional sobre inclusión educativa a la práctica diaria en el aula: Una revisión de la literatura - Claudia Pulido Toro (Corporación Universitaria Minuto de Dios, 2024)
The demands faced by teachers when dealing with diversity are prompting several countries to reform professional learning (PL) policy to support sustainable learning opportunities for all. As inclusive education (IE) unfolds within a complex dynamic, it is essential to consider how different elements interact during PL deployment in context. There are potential tensions between government policy, the traditional special needs orientation of PL programs, and the fact that IE definition and practice differ from one instance to another. There is currently limited research on how PL is being transferred to the classroom. This article reviews scholarly evidence concerning four domains that have been studied separately but not integrated as a whole in inclusion education inquiry: Inclusive education, inclusive practice, teacher learning and professional learning. The purpose of this review is threefold: (i) to provide an overview of the evolution of the concept of IE and the context of the contemporary reform of Education For All; (ii) to understand how inclusive practice is permeated by developments in IE and their implications; and (iii) to critically examine different research perspectives on PL in IE and illustrate the value of a complexity approach that encompasses macro, micro, and mesoscale elements that combine to describe IE's complex phenomena.